GUIDELINES FOR PROMOTING MUSHROOM FARMING IN COMMUNITIES.A CASE STUDY OF MUSHROOM FARM, POLICE SERGEANT MAJOR WICHIANKONGJUI, VILLAGE NO. 9, ROMMUEANG SUBDISTRICT, MUEANG DISTRICT, PHATTHALUNG PROVINCE THAILAND - Mastuwach , Trirat; Dumrongwattana, Jittima; Khaenamkaew, Daycho; Dechochai, Udomsak (Journal of MCU Phetchaburi Review, 2021)
This research paper aims to study the methods of mushroom farming. To analyze the problem condition of mushroom farming and learn how to promote mushroom farming case study of mushroom farm Wichian Kongjui police sword using qualitative research protocols 11 key informants collected data using an interview form, participant observation. Voice recorder, camera, descriptive data analysis the study results showed that 1) mushroom farming methods It was found that the essential steps were as follows: 1.1) Selection of mushroom species from more than 10 species. 1.2) Mushroom cultivation by mushroom inoculation method 1.3) Mushroom care by watering 1.4) Mushroom picking by hand pull method 2) The problem of mushroom farming was found. 2.1) there is too much moisture in the raw materials causing spoilage of sawdust, 2.2) problems with fungal and insect diseases, 2.3) problems with low mushroom prices, and 3) promotion guidelines for mushroom farming, found that 3.1) promotion of package designs that Beautiful 3.2) Guidelines for using natural extracts to get rid ozf insects 3.3) Distribution agents 3.4) Online distribution or selling at department stores and selling in front of the farm. 4) Recommendations 4.1) There should be a market to support the produce from the farm. 4.2) The greenhouses for mushroom cultivation should be completely closed. Know different communities to extend products in the community 4.4) The state should promote and educate marketing. And product price assurance. 4.5) There should be a promotion in determining the use of pesticides and fungicides that are pests of mushrooms.